2010
DOI: 10.1007/s00415-010-5563-y
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of MRI-detected atrophy in secondary progressive multiple sclerosis

Abstract: MRI measures of tissue atrophy within the central nervous system may reflect the neurodegenerative process which underpins the progressive phase of multiple sclerosis (MS). There has been limited longitudinal investigation of MRI-detected atrophy in secondary progressive MS. This study includes 56 subjects with secondary progressive MS. Subjects were followed up for 2 years and MRI analysis was conducted at 12 month intervals using the following measures: (1) whole brain (WB) volume change; (2) grey and white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 45 publications
4
42
2
1
Order By: Relevance
“…Such discrepancies might be due to differences in sample sizes, follow-up durations and techniques employed to measure cord CSA. Also, the association between longitudinal modification of cord CSA and clinical worsening is discordant among studies, with some studies describing such a relationship [16,17,21] while others not [5,[18][19][20]. Probably due to the fact that the optimal method for measuring cervical cord atrophy has not yet been identified, only a small number of clinical trials [17,23,24] have used cord CSA as an exploratory endpoint.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Such discrepancies might be due to differences in sample sizes, follow-up durations and techniques employed to measure cord CSA. Also, the association between longitudinal modification of cord CSA and clinical worsening is discordant among studies, with some studies describing such a relationship [16,17,21] while others not [5,[18][19][20]. Probably due to the fact that the optimal method for measuring cervical cord atrophy has not yet been identified, only a small number of clinical trials [17,23,24] have used cord CSA as an exploratory endpoint.…”
Section: Introductionmentioning
confidence: 88%
“…Conversely, only a few studies have examined spinal cord atrophy progression. A progressive reduction of cervical cord cross-sectional area (CSA) has been shown to occur in MS [5,[16][17][18][19][20][21], although the annual rate of cord volume loss is highly variable across studies, ranging from 1 % [20] to 5.2 % [22], with the majority of studies showing a yearly volume loss around 2-3 % [5,16,17,19,21]. Such discrepancies might be due to differences in sample sizes, follow-up durations and techniques employed to measure cord CSA.…”
Section: Introductionmentioning
confidence: 92%
“…6,8,9,13,17,21,22 However, Lukas et al 9 recently reported that spinal cord tissue loss may slow down over time, with already highly atrophied structures exhibiting slower atrophy rates. Our results support this notion: over the lengthy followup period we found a smaller annualized CSA loss than other studies with a shorter follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 This discrepancy may be explained by several factors, such as differing sample sizes, follow-up periods, and methods used to measure the cord CSA. 7,[13][14][15] Although some cross-sectional studies 11,12 have demonstrated the value of spinal cord atrophy as an independent predictor of clinical outcome, only a few longitudinal studies 9,16,17 have specifically focused on analyzing the clinical relevance of this finding in MS patients, and these include a short follow-up or were not focused on PPMS.…”
Section: Introductionmentioning
confidence: 99%
“…Most current MRI studies of the cord use a spatial resolution of B1 mm 2 in each plane, which is B1% of the cord CSA. As atrophy is a slow process, with an annual atrophy rate of about À1.6% observed in secondary progressive MS patients, 11 a resolution of 1 mm 2 can be considered coarse, and a high methodological sensitivity is essential to accurately estimate the true rate of change on current MRI data. A number of reproducible image analysis methods of measuring CSA are now in use; [12][13][14] however, other factors may still confound CSA measurement.…”
Section: Introductionmentioning
confidence: 99%